Multi-scale constructed high-transparency stable super-hydrophobic coating and preparation method thereof

Through a multi-scale construction method, micron-scale hollow particles and nanoparticles are used to form a superhydrophobic coating with high transparency and stability, solving the problems of fragility and insufficient stability of existing coatings, and achieving dual improvements in transparency and anti-fouling performance.

CN119608545AActive Publication Date: 2025-03-14UNIV OF ELECTRONICS SCI & TECH OF CHINA +2

Patent Information

Application Number
CN202411638517.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-17
Publication Date
2025-03-14
Estimated Expiration
2044-11-17

AI Technical Summary

Technical Problem

The existing transparent superhydrophobic coatings have problems of fragile coatings and insufficient stability.

Method used

Through a multi-scale construction method, micron-scale hollow particles are used to form a superhydrophobic coating with high transparency and stability. Specific steps include preparing PS@SiO2 particles, forming a single layer arrangement coating, pyrolysis treatment, chemical vapor deposition and hydrophobic modification of nanoparticles.

Benefits of technology

A superhydrophobic coating with high transparency and stability is achieved, with good antifouling properties and mechanical strength, and can maintain superhydrophobic properties for a long time in practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608545A_ABST
    Figure CN119608545A_ABST
Patent Text Reader

Abstract

The invention provides a multi-scale constructed high-transparency stable super-hydrophobic coating and a preparation method thereof, multi-scale coupling is introduced to prepare a transparent super-hydrophobic surface, that is, a micron-sized hollow particle and nano-particle collaborative accumulation mode is adopted, and the micron-sized hollow particles can play a supporting role while ensuring the transparency of the micron-sized hollow particles; the diameter of the coupled nanoparticles is about dozens of nanometers and is smaller than one tenth of the wavelength of visible light, so that the influence of Mie scattering and Rayleigh scattering can be reduced to the greatest extent, and high transparency is kept. Meanwhile, the stability of the surface is optimized, it is ensured that the super-hydrophobic surface can achieve the excellent antifouling effect in practical application, and the transparency and mechanical strength of the material are not sacrificed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of super-hydrophobic materials, and in particular relates to a multi-scale highly transparent and stable super-hydrophobic coating and a preparation method thereof. Background Art

[0002] At present, the mainstream scheme for preparing transparent super-hydrophobic coatings mostly uses nanoparticles with a size of less than 100nm. The self-similar structure formed by the accumulation of nanoparticles has excellent anti-wetting properties, thereby effectively improving the weather resistance of the coating. However, the transparent super-hydrophobic surface coating formed by this nanoparticle accumulation structure has the defects of fragile coating and insufficient stability.

[0003] Researchers are committed to exploring various methods to achieve super-hydrophobic surfaces that meet transparency requirements. Patent CN117925047A uses epoxy resin and silane coupling to prepare transparent solvents, and obtains transparent super-hydrophobic coatings by immersion or spraying. However, the coating obtained by this method contains organic resins, is easy to age, and has poor weather resistance. Patent CN115404004A uses silane coupling agents to combine with silicon dioxide to form a nano-stacked structure, but its stability is poor and the surface structure is difficult to persist. Summary of the invention

[0004] The purpose of the present invention is to propose a multi-scale highly transparent and stable super-hydrophobic coating and a preparation method thereof, so as to solve the technical problems of the existing coatings mentioned in the above background technology that the coatings are fragile and have insufficient stability.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a multi-scale highly transparent and stable super-hydrophobic coating comprises the following steps:

[0007] (1) Polystyrene (PS) microspheres were selected as hard templates, and an alcohol solution was used as a medium. Tetraethyl silicate or SiCl4 was added, and an acid or base was used as a catalyst to form a silica shell on the surface of the PS microspheres to prepare PS@SiO2 particles;

[0008] (2) preparing a PS@SiO2 aqueous dispersion from the PS@SiO2 particles obtained in step (1); immersing the modified substrate in the PS@SiO2 aqueous dispersion to obtain a single-layer PS@SiO2 coating on the substrate;

[0009] (3) drying the coated substrate obtained in step (2) in air and placing it in a muffle furnace, gradually raising the temperature in the furnace to a specified temperature according to a predetermined heating program, maintaining the temperature after reaching the specified temperature, and then naturally cooling it to room temperature along with the furnace;

[0010] (4) forming a layer of SiO2 on the surface of the substrate obtained in step (3) by chemical vapor deposition;

[0011] (5) Immersing the substrate obtained in step (4) in SiO2 nanoparticle sol to form a micro-nano composite structure, and performing hydrophobic modification on the nanoparticles using a gas / liquid phase method.

[0012] Furthermore, in step (1), the alcohol is ethanol, the catalyst is concentrated aqueous ammonia, and the ratio of each substance in the reaction is: PS microspheres: ethanol: tetraethyl silicate: concentrated aqueous ammonia = 0.3g: 40ml: 0.2ml: 1.6ml, and the mass fraction of the concentrated aqueous ammonia is 25-28.

[0013] Furthermore, in step (2), the modification treatment refers to treating the substrate with a plasma cleaner to make it positively charged, then immersing the substrate in a toluene solution of an amino-terminated silane coupling agent, and then protonating it with hydrochloric acid; the concentration of the PS@SiO2 aqueous dispersion is 5 mg / ml.

[0014] Furthermore, in step (3), the predetermined heating program refers to raising the temperature to 400°C at a rate of 4-5°C / min and keeping the temperature for 2 hours.

[0015] Furthermore, in step (4), the chemical vapor deposition method refers to placing the substrate obtained in step (3) together with two glass bottles containing 4 ml of tetraethyl silicate and 4 ml of ammonia water respectively into a vacuum tank and sealing them for 24 hours.

[0016] Furthermore, the alcohol is selected from any one of ethanol, propanol, isopropanol, acetone, and ethyl acetate, the PS microspheres are submicron particles with a size of 500-800 nm, the acid catalyst used for catalysis mainly includes H2SO4, H3PO4, HCl aqueous solution, acetic acid, etc., and the base catalyst mainly includes NaOH aqueous solution, KOH aqueous solution, ammonia water, etc.

[0017] Furthermore, the amino-terminated silane coupling agent is selected from any one of triaminopropyltriethoxysilane, triaminopropyltrimethoxysilane and (3-aminopropyl)dimethylethoxysilane.

[0018] Furthermore, in step (5), the hydrophobic modification of the nanoparticles is achieved by a hydrolysis condensation reaction between the organic silane coupling agent and the nanoparticles.

[0019] Furthermore, the organosilane coupling agent includes a fluorine-containing organosilane coupling agent and a fluorine-free organosilane coupling agent; the fluorine-free organosilane coupling agent includes KH-550, KH-540, KH-902, and KH-554; the fluorine-containing organosilane coupling agent includes perfluorodecyltrichlorosilane, perfluorohexyltrichlorosilane, perfluorooctyltrichlorosilane, perfluorododecyltrichlorosilane, perfluorohexyltrimethoxysilane, perfluorooctyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorohexyltriethoxysilane, perfluorooctyltriethoxysilane, and perfluorodecyltriethoxysilane.

[0020] Another object of the present invention is to provide a highly transparent and stable super-hydrophobic coating with a multi-scale structure prepared by the above method.

[0021] The present invention has the following beneficial effects:

[0022] The present invention introduces multi-scale coupling to prepare a transparent super-hydrophobic surface, that is, the micron-sized hollow particles and nanoparticles are co-stacked. The micron-sized hollow particles can play a supporting role while ensuring its transparency; the coupled nanoparticle size is about 40nm, which is less than one tenth of the wavelength of visible light, and can minimize the influence of Mie scattering and Rayleigh scattering, thereby maintaining high transparency. At the same time, the stability of the surface is optimized to ensure that the super-hydrophobic surface can achieve excellent anti-fouling effects in practical applications without sacrificing the transparency and mechanical strength of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0024] Figure 1 Schematic diagram of the process for preparing PS@SiO2 particles;

[0025] Figure 2 Schematic diagram of the process of obtaining a monolayer aligned PS@SiO2 coating;

[0026] Figure 3 This is a scanning electron microscope morphology of submicron-scale monolayer microspheres;

[0027] Figure 4 This is the image before pyrolysis;

[0028] Figure 5 This is the image after pyrolysis;

[0029] Figure 6 This is the scanning electron microscope morphology after vapor deposition;

[0030] Figure 7 The scanning electron microscope morphology of the super hydrophobic coating;

[0031] Figure 8 This is a picture of the water contact angle of the superhydrophobic coating;

[0032] Fig. 9 It is a comparison chart of the results of temperature shock test, alternating humidity and heat test, salt spray test and anti-algae adhesion test;

[0033] Fig.10 The transmittance measurement result. DETAILED DESCRIPTION

[0034] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] See also Figure 1-10 As shown, a multi-scale highly transparent and stable super-hydrophobic coating and a preparation method thereof specifically include the following steps:

[0036] Step 1: Preparation of PS@SiO2 particles.

[0037] Polystyrene (PS) microspheres were selected as templates, and alcohol solutions were used as media. Tetraethyl silicate (TEOS) or SiCl4 was added under the catalysis of acid or base to form a silica shell on the surface of the PS microspheres.

[0038] In this step, the alcohol is selected from any one of ethanol, propanol, isopropanol, acetone, and ethyl acetate; the polystyrene (PS) microspheres are submicron particles with a size of 500-800nm; the acid catalysts used for catalysis mainly include H2SO4, H3PO4, HCl aqueous solution or acetic acid, and the base catalysts mainly include NaOH aqueous solution, KOH aqueous solution or ammonia water.

[0039] Taking the ethanol medium and ammonia catalytic system as an example, PS microspheres were dissolved in the ethanol solution to form a PS ball solution, which was continuously stirred to achieve the purpose of dispersion. TEOS and concentrated ammonia were added in a volume ratio of 1:8, and the stirring was continued for 24 hours to complete the The PS@SiO2 particles are obtained by centrifugation. Figure 1As shown. The ratio of each substance in the reaction is: PS microspheres: ethanol: tetraethyl silicate: concentrated ammonia water = 0.3g: 40ml: 0.2ml: 1.6ml. The mass fraction of concentrated ammonia water is 25-28.

[0040] Step 2: Arrangement of PS@SiO2 particles on the substrate.

[0041] First, the particles obtained in step 1 are prepared into a PS@SiO2 aqueous dispersion of about 5 mg / ml, ready for assembly and arrangement on a substrate; then, the substrate is modified and treated with a plasma cleaning machine to make it positively charged, and then the substrate is immersed in a toluene solution of an amino-terminated silane coupling agent for 30 minutes, and then protonated with hydrochloric acid; finally, the positively charged substrate is immersed in a 5 mg / ml PS@SiO2 aqueous dispersion for 30 minutes, thereby obtaining a single-layer arranged PS@SiO2 coating. The process of this step is as follows: Figure 2 shown. Figure 3 This is a scanning electron microscope morphology of submicron-scale monolayer arranged microspheres.

[0042] In this step, the amino-terminated silane coupling agent is selected from any one of triaminopropyltriethoxysilane, triaminopropyltrimethoxysilane, and (3-aminopropyl)dimethylethoxysilane.

[0043] Step three: pyrolysis to improve coating transparency.

[0044] The introduction of micron-sized particles will provide a certain support effect, but it will inevitably reduce the transparency of the coating, so it needs to be made transparent to form submicron-sized hollow particles arranged in an orderly manner on the substrate, which can both ensure transparency and provide support.

[0045] The substrate with coating obtained in step 2 is placed in air for drying and then placed in a muffle furnace. The temperature is raised to 400°C at a rate of 4-5°C / min and maintained at this temperature for 2 hours, and then the furnace is allowed to cool naturally to room temperature. After calcination, the PS@SiO2 particles become hollow microspheres, and the transparency of the coating is significantly improved. Figure 4 is the image before pyrolysis, Figure 5 This is the image after pyrolysis.

[0046] Step 4: Vapor deposition improves coating stability.

[0047] In situ inorganic cross-linking is used to further increase the adhesion between the hollow microspheres and the substrate, thereby improving the strength of the hollow microspheres as a skeleton. In situ growth cross-linking is performed by growing silica using chemical vapor deposition.

[0048] The substrate obtained in step 3 was placed in a vacuum tank together with two glass bottles containing 4 ml of tetraethyl silicate (TEOS) and 4 ml of ammonia water respectively, and subjected to chemical vapor deposition (CVD) growth for 24 hours to form a layer of SiO2 on its surface, thereby improving the stability of the coating. Figure 6 This is a scanning electron microscope image of the vapor deposition.

[0049] Step 5: Composite nanoparticles

[0050] The substrate obtained in step 4 is immersed in SiO2 nanoparticle sol for 10 minutes to form a micro-nano composite structure, and the nanoparticles are hydrophobically modified by a gas / liquid phase method, for example, by a hydrolysis condensation reaction between an organic silane coupling agent and the nanoparticles to achieve hydrophobic modification of the nanoparticles. Figure 7 Scanning electron microscopy morphology of highly transparent and stable superhydrophobic coating constructed at multiple scales. Figure 8 This is a picture of the water contact angle of the superhydrophobic coating. The water contact angle is 152.9°, which has excellent superhydrophobic properties.

[0051] The organosilane coupling agent described in this step includes fluorine-containing organosilane coupling agent and fluorine-free organosilane coupling agent; the fluorine-free organosilane coupling agent includes KH-550, KH-540, KH-902, and KH-554; the fluorine-containing organosilane coupling agent includes perfluorodecyltrichlorosilane, perfluorohexyltrichlorosilane, perfluorooctyltrichlorosilane, perfluorododecyltrichlorosilane, perfluorohexyltrimethoxysilane, perfluorooctyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorohexyltriethoxysilane, perfluorooctyltriethoxysilane, and perfluorodecyltriethoxysilane.

[0052] In order to verify the performance of the coating, environmental tests were carried out including temperature shock test, alternating humidity and heat test, salt spray test and anti-algae adhesion test.

[0053] Temperature shock test: The coating is kept at 70℃±2℃ and -46℃±2℃ for 2h for one cycle. After 5 cycles of testing and returning to normal temperature, the water contact angle has no obvious change, and the film has no defects such as peeling, delamination, cracks, and blistering. Alternating heat and humidity test: The transparent super hydrophobic coating is kept at 50℃±2℃ and 95%-100% relative humidity for 24h for one cycle. After 5 cycles of testing and returning to normal temperature, the water contact angle decreases by about 1°, and the film has no defects such as peeling, delamination, cracks, and blistering. Salt spray test: 24 hours of salt spray and 24 hours of drying are one cycle, and 5 cycles are performed. The coating still has super hydrophobicity. Anti-algae adhesion experiment: The sample is immersed in a Chlorella solution at an ambient temperature of 25℃, and the initial algae concentration is ensured to be greater than 10 8 cm -3After 5 consecutive days of observation and experiment, the surface of the blank control sample showed salt and algae adhesion at different time points (day 1, day 3, and day 5). In contrast, the transparent super-hydrophobic sample did not show any salt or algae adhesion on its surface during the entire 5-day test. Moreover, after 5 days of experiment, the transparent super-hydrophobic sample still maintained its super-hydrophobic properties.

[0054] Fig. 9 The results of the temperature shock test, alternating humidity and heat test, salt spray test and anti-algae adhesion test are compared. It can be seen that after various environmental tests such as temperature shock test, alternating humidity and heat test, salt spray test and anti-algae adhesion test, the coating still maintains the self-cleaning super-hydrophobic property, which shows that the coating has good stability.

[0055] Fig.10 The transmittance measurement results are given. According to the data in the figure, the overall transmittance loss of the transparent super-hydrophobic coating is about 5%. Compared with other transparent super-hydrophobic coating preparation schemes with better stability, the transmittance loss is correspondingly smaller.

[0056] The present invention introduces multi-scale coupling to prepare a transparent super-hydrophobic surface, that is, a method of co-stacking micron-sized hollow particles and nanoparticles. Micron-sized hollow particles can play a role of supporting and increasing stability while ensuring its transparency; nanoparticle stacking can provide transparency and super-hydrophobicity. The microstructure adopts microspheres as building units, and uses its single concave, controllable and orderly arranged structure to improve hydrophobicity; the microspheres adopt a hollow structure to improve light transmittance; the microspheres enhance the binding force between the particles and the substrate through physical cross-linking to improve stability. Nanoparticles adopt a diameter of about tens of nanometers to reduce scattering and improve their light transmittance; the nanostructure adopts controllable stacking to improve super-hydrophobicity; the nanostructure adopts a self-similar structure to improve the weather resistance of the structure.

[0057] The unique properties of the super-hydrophobic structure of the present invention can effectively prevent the attachment of pollutants, thereby ensuring the clarity and durability of key components. The super-hydrophobic structure can be used for surfaces with high transparency requirements such as automobile windshields, solar panels, camera lenses, and marine optical windows.

[0058] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well.

Claims

1. A method for preparing a highly transparent and stable super-hydrophobic coating constructed on a multi-scale basis, characterized in that: The specific steps include: (1) Polystyrene (PS) microspheres were selected as templates, alcohol solutions were used as media, tetraethyl silicate or SiCl4 was added, and acid or base was used as catalyst to form a silica shell on the surface of PS microspheres to prepare PS@SiO2 particles; (2) preparing a PS@SiO2 aqueous dispersion from the PS@SiO2 particles obtained in step (1); immersing the modified substrate in the PS@SiO2 aqueous dispersion to obtain a single-layer PS@SiO2 coating on the substrate; (3) drying the coated substrate obtained in step (2) in air and placing it in a muffle furnace, gradually raising the temperature in the furnace to a specified temperature according to a predetermined heating program, maintaining the temperature after reaching the specified temperature, and then naturally cooling it to room temperature along with the furnace; (4) forming a layer of SiO2 on the surface of the substrate obtained in step (3) by chemical vapor deposition; (5) Immersing the substrate obtained in step (4) in SiO2 nanoparticle sol to form a micro-nano composite structure, and then hydrophobically modifying the nanoparticles using a gas / liquid phase method.

2. The method for preparing a multi-scale highly transparent and stable super-hydrophobic coating according to claim 1, characterized in that: In step (1), the alcohol is ethanol, the catalyst is concentrated aqueous ammonia, and the ratio of each substance in the reaction is: PS microspheres: ethanol: tetraethyl silicate: concentrated aqueous ammonia = 0.3g: 40ml: 0.2ml: 1.6ml, and the mass fraction of the concentrated aqueous ammonia is 25-28.

3. The method for preparing a highly transparent and stable super-hydrophobic coating constructed on a multi-scale basis according to claim 1, characterized in that: In step (2), the modification treatment refers to treating the substrate with a plasma cleaner to make it positively charged, then immersing the substrate in a toluene solution of an amino-terminated silane coupling agent, and then protonating it with hydrochloric acid; the concentration of the PS@SiO2 aqueous dispersion is 5 mg / ml.

4. The method for preparing a highly transparent and stable super-hydrophobic coating with a multi-scale structure according to claim 2 or 3, characterized in that: In step (3), the predetermined heating program refers to raising the temperature to 400°C at a rate of 4-5°C / min and maintaining the temperature.

5. The method for preparing a highly transparent and stable super-hydrophobic coating with a multi-scale structure according to claim 2 or 3, characterized in that: In step (4), the chemical vapor deposition method refers to placing the substrate obtained in step (3) and two glass bottles containing 4 ml of tetraethyl silicate and 4 ml of ammonia water respectively into a vacuum tank and sealing it.

6. The method for preparing a multi-scale highly transparent and stable super-hydrophobic coating according to any one of claims 1 to 3, characterized in that: The alcohol is selected from any one of ethanol, propanol, isopropanol, acetone, and ethyl acetate. The PS microspheres are submicron particles with a size of 500-800 nm. The acid catalyst used for catalysis mainly includes H2SO4, H3PO4, HCl aqueous solution, acetic acid, etc., and the base catalyst mainly includes NaOH aqueous solution, KOH aqueous solution, ammonia water, etc.

7. The method for preparing a multi-scale highly transparent and stable super-hydrophobic coating according to claim 3, characterized in that: The amino-terminated silane coupling agent is selected from any one of triaminopropyltriethoxysilane, triaminopropyltrimethoxysilane and (3-aminopropyl)dimethylethoxysilane.

8. A method for preparing a multi-scale highly transparent and stable super-hydrophobic coating according to any one of claims 1 to 3 and 7, characterized in that: In step (5), the hydrophobic modification of the nanoparticles is achieved by hydrolyzing and condensing the organic silane coupling agent with the nanoparticles.

9. The method for preparing a multi-scale highly transparent and stable super-hydrophobic coating according to claim 8, characterized in that: The organic silane coupling agent includes a fluorine-containing organic silane coupling agent and a fluorine-free organic silane coupling agent; the fluorine-free organic silane coupling agent includes KH-550, KH-540, KH-902, and KH-554; the fluorine-containing organic silane coupling agent includes perfluorodecyltrichlorosilane, perfluorohexyltrichlorosilane, perfluorooctyltrichlorosilane, perfluorododecyltrichlorosilane, perfluorohexyltrimethoxysilane, perfluorooctyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorohexyltriethoxysilane, perfluorooctyltriethoxysilane, and perfluorodecyltriethoxysilane.

10. A highly transparent and stable super-hydrophobic coating with a multi-scale structure prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silicon dioxide hollow sphere / polystyrene composite heat insulating material and method for preparing same

    CN101585948A

  • Preparation method for super-hydrophobic surface with bionic micro-nano composite structure

    CN105413994A

  • Preparation method of transparent super-amphiphobic hot water and hot oil coating

    CN105562314A

  • Method for preparing transparent superhydrophobic surface

    CN108623188A

  • Super-hydrophobic self-cleaning antifouling nano-film and PECVD preparation method

    CN109536920A

Cited By

  • Fluorine-free transparent super-hydrophobic coating with high environmental stability and preparation method thereof

    CN121895858A